The ethical leadership of school administrators that affects the organization's affiliation. Loei Primary Educational Service Area Office 2: The ethical leadership of school administrators that affects the organization's affiliation. Loei Primary Educational Service Area Office 2 - Hatammawong, Nadtakorn; Sod-ium, Pim-on (RATANABUTH JOURNAL, 2023)
The school is one of the most important organizations in education management in Thailand. Success in educational management is possible because of the teacher as an important component. In its main role in teaching and learning, it is a driving force to achieve the goal of effective education management. The quality of education is therefore the result of the quality of teachers who willingly pursue their careers. It is related to the factors of engagement to manage the organization successfully so it depends on the executive model and the most important executive style that makes personnel engagement in the organization is an executive with ethical leadership is very important in the educational organization because the most important duty of an educational administrator is to have ethics in school management. The objectives of this research are 1) to study the level of ethical leadership of school administrators, affiliated with Loei Primary Educational Service Area Office2, 2) to study the level of engagement with teachers' organizations. It is affiliated with Loei Primary Educational Service Area Office2 3) To study the relationship between the ethical leadership of school administrators and the teacher's organizational affiliation. It is affiliated with Loei Primary Educational Service Area Office2 4) To study the ethical leadership of school administrators that affects teachers' organizational engagement. It is affiliated with Loei Primary Educational Service Area Office 2 and 5) to create an affiliation equation for teachers' organizations. It is affiliated with Loei Primary Educational Service Area Office2 Samplers of research are school administrators and teachers, affiliated with Loei Primary Educational Service Area Office2, 2022, 400 students, the accuracy of both individual and individual questionnaires was found to be between 0.859-0.976. Find percentages, averages, and standard deviations. Statistics used to test hypotheses include Pearson's correlation coefficient determination and multiple regression analysis. The results showed that 1) Ethical leadership of school administrators, affiliated with Loei Primary Educational Service Area Office2, as a whole and on all sides, is at a very high level. 2) Affiliation with the organization of teachers It is affiliated with the Loei Primary Educational Service Area Office2 as a whole is at the highest level, and the side is at the highest level. 3) Ethical leadership of school administrators, affiliated with Loei Primary Educational Service Area Office2, as a whole, has a positive correlation with the teacher's organization. It is statistically significantly high (r=.693) at the .01 level. 4) Ethical leadership of school administrators consists of respect and respect. Governance engagement and Trust It affects the teacher’s engagement with the organization. It is affiliated with Loei Primary Educational Service Area Office 2 was statistically significant at .01 with a predictive efficiency of 49.10 percent